Triple checkpoint blockade of PD-1, Tim-3, and Lag-3 enhances adoptive T cell immunotherapy in a mouse model of ovarian cancer - Alencar, Gabriel F; Mohamed, Asmaa O; Burnett, Madison G; Jean, Samantha St; Nelson, Anders R; Su, Yapeng; Voillet, Valentin; Bates, Breanna M; Rodgers Suarez, Magdalia; Ruskin, Susan L; Trieu, Lam; Lam, Jennifer L; et al. (Proceedings of the National Academy of Sciences - PNAS, 2025)
The five-year survival rate for ovarian cancer patients remains below 50%, underscoring the need for innovative therapies. One promising approach involves engineering T cells to specifically target proteins uniquely overexpressed in tumors, thereby controlling tumor growth without toxicity to healthy tissues. Mesothelin (MSLN) contributes to the malignant and invasive phenotype in ovarian cancer and has limited expression in healthy cells, making it a candidate immunotherapy target. Our previous results in a mouse model of ovarian cancer demonstrated that T cells engineered to express a T cell receptor (TCR) targeting MSLN (TCR ) mediated therapeutic activity, delaying tumor growth and prolonging mouse survival. However, inhibitory ligands expressed in the tumor microenvironment (TME) interacted with inhibitory receptors on activated T cells, suppressing antitumor function. We hypothesized combining engineered T cells with checkpoint blockade would enhance T cell function and improve therapeutic efficacy, but administration of monospecific antibodies targeting individual inhibitory pathways had no significant impact on T cell efficacy. By contrast, the combination of PD-1, Tim-3, and Lag-3 blockade with engineered T cells significantly improved T cell function and overall animal survival relative to treatment with antibody alone or TCR with singlet or doublet antibody combinations. Single-cell RNA sequencing revealed TCR T cells treated with the triplet antibody combination increased expression of genes involved in interferon responses and metabolic function, and reduced expression of genes associated with exhaustion. These results suggest that strategies to disrupt multiple inhibitory pathways simultaneously may be necessary for improved adoptive T cell therapy efficacy in patients.